Lifestyle factors in neurological diseases: Mechanisms, evidence, and experience perspectives. - Xasanov Azizbek Murod o’g’li; Xidirov Ziyadulla Erkinovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Lifestyle factors such as diet, physical activity, sleep, and stress management play crucial roles in the onset and progression of neurological diseases. Emerging evidence demonstrates that these behaviors modulate key mechanisms including neuroinflammation, oxidative stress, and vascular regulation. Integrating multidisciplinary findings, this study emphasizes how modifiable habits can either promote neuroprotection or accelerate neurodegeneration. The paper highlights translational strategies aimed at applying lifestyle-based interventions in clinical and public-health settings to improve neurological outcomes.